Analysis of Symbols and Meanings of the Anthology of Autumn Tears of Poetry by Fakhrunnas Ma Jabbar - Yuliarza Putri; Sudirman Shomary (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Words in poetry usually contain symbols and figurative meanings. Given the importance of symbols and figurative meanings in understanding the message in poetry, the authors are interested in conducting a research entitled "Analysis of symbols and figurative meanings of the Anthology of Autumn Tears by Fakhrunnas Ma Jabbar". The problem studied in this problem is how are the symbols contained in the Anthology of Autumn Tears by Fakhrunnas Ma Jabbar? What is the figurative meaning contained in the Anthology of Autumn Tears by Fakhrunnas Ma Jabbar? The purpose of this study is to describe, analyze, and conclude the problems that have been described in the formulation of the problem, namely: the symbols contained in the Anthology of Autumn Tears of Poetry by Fakhrunnas Ma Jabbar, the figurative meanings contained in the Anthology of Autumn Tears of Poetry by Fakhrunnas Ma Jabbar. The theory used to examine or analyze this research is the theory of Sobur (2009) about symbols and Pradopo (2012) about figurative meanings, as well as other supporting theories. The data of this study were taken from the collection of poems, Tears of Autumn by Fakhrunnas Ma Jabbar. The method used is descriptive method. The approach used in this research is a qualitative approach. This type of research is library research. Data collection techniques using hermeneutic techniques. The results of this study are that there are 17 data symbols in the Anthology of Autumn Tears Poetry by Fakhrunnas Ma Jabbar. Meanwhile, in the figurative meaning, the writer finds 33 data. The figurative meaning consists of the figurative meaning of comparison (simile) as much as 5 data, the figurative meaning of metaphor 3 data, the figurative meaning of epic 3 data, the figurative meaning of allegory 2 data, the figurative meaning of personification 20 data, as well as the figurative meaning of metonymy and synecdoc cannot be found in this study. . So the figurative meaning that is more dominant in this study is the figurative meaning of personification as much as 20 data, this is because this figurative meaning can give a shadow or wish to become a real picture. By using this figurative meaning, the author is easier to imagine in his work. Meanwhile, the least found aspect is the figurative meaning of metonymy and synecdoche because these figurative meanings are rarely used in a poem.